Chemogenomic Screening in a Patient‐Derived 3D Fatty Liver Disease Model Reveals the CHRM1‐TRPM8 Axis as a Novel Module for Targeted Intervention - Sonia Youhanna; Aurino M. Kemas; Shane C. Wright; Yi Zhong; Britta Klumpp; Kathrin Klein; Aikaterini Motso; Maurice Michel; Nicole Ziegler; Mingmei Shang; Pierre Sabatier; Aimo Kannt; et al. (Advanced Science)
Abstract Metabolic dysfunction‐associated steatohepatitis (MASH) is a leading cause of chronic liver disease with few therapeutic options. To narrow the translational gap in the development of pharmacological MASH treatments, a 3D liver model from primary human hepatocytes and non‐parenchymal cells derived from patients with histologically confirmed MASH was established. The model closely mirrors disease‐relevant endpoints, such as steatosis, inflammation and fibrosis, and multi‐omics analyses show excellent alignment with biopsy data from 306 MASH patients and 77 controls. By combining high‐content imaging with scalable biochemical assays and chemogenomic screening, multiple novel targets with anti‐steatotic, anti‐inflammatory, and anti‐fibrotic effects are identified. Among these, activation of the muscarinic M1 receptor (CHRM1) and inhibition of the TRPM8 cation channel result in strong anti‐fibrotic effects, which are confirmed using orthogonal genetic assays. Strikingly, using biosensors based on bioluminescence resonance energy transfer, a functional interaction along a novel MASH signaling axis in which CHRM1 inhibits TRPM8 via Gq/11 and phospholipase C‐mediated depletion of phosphatidylinositol 4,5‐bisphosphate can be demonstrated. Combined, this study presents the first patient‐derived 3D MASH model, identifies a novel signaling module with anti‐fibrotic effects, and highlights the potential of organotypic culture systems for phenotype‐based chemogenomic drug target identification at scale.